CULTURAL SIGNIFICANCE OF KRAPYAK, YOGYAKARTA: LOCAL COMMUNITY PERCEPTIONS OF A HISTORIC URBAN LANDSCAPE - Asrofah Afnidatul Khusna; Grizzly Akbar Rizkyka Ananda (Kalyanamitra: Journal of Archaeological Resource Management, 2025)
Cultural heritage management strategies should be based on the cultural significance of heritage itself. However, government policies often focus solely on preserving cultural heritage as individual physical objects, neglecting its deeper role in shaping collective identity. This study aims to explore the cultural significance of the Krapyak area from the perspective of the local community. As part of Cosmological Axis of Yogyakarta, Krapyak is recognized as a Historic Urban Landscape with cultural and historical importance. Using a deductive qualitative approach, this study collects data through literature review, observations, and interviews. This study reveals that, beyond the well-known Panggung Krapyak, the local community also considers Umbul Krapyak to hold cultural significance tied to their collective memory, despite its physical absence. Additionally, the presence of three Islamic boarding schools in the area has played a key role in shaping social and economic interactions. Moreover, the community acknowledges the significance of intangible cultural heritage, particularly traditional lurik weaving, which remains an integral part of their cultural identity.